Key Points of OXC Technology and Application Strategy - Wei, Peng; Li, Guo; Wang, Kexin (Journal of Artificial Intelligence and Information, 2025)
This article elaborates on the technical characteristics and engineering design principles of Optical Cross-Connect (OXC) technology from various perspectives, including its advantages, application scenarios, and design essentials. It highlights that in the era of algorithmic networks, to meet the requirements of ubiquitous access, high-speed interconnection, and flexible scheduling in an all-optical infrastructure system, the OXC/ROADM+OTN optical-electronic integrated system will become the next-generation transmission network.